Clinical correlates and adverse outcomes of ADHD, disruptive behavior disorder and their co-occurrence among children and adolescents with HIV in Uganda. Issue 11 (1st November 2020) - Taylor Salisbury, Tatiana; Kinyanda, Eugene; Levin, Jonathan; Foster, Alexander; Mpango, Richard; Patel, Vikram; Gadow, Kenneth D.
ABSTRACT: Attention-deficit/hyperactivity disorder (ADHD), oppositional defiant disorder (ODD), and conduct disorder (CD) are important mental health concerns among children and adolescents living with HIV (CA-HIV). This study examines clinical correlates and adverse outcomes associated with ADHD, ODD/CD and ADHD + ODD/CD among ( N = 1, 336) CA-HIV living in Uganda. Being male, higher socio-economic status, emotional disorder, greater caregiver distress and youth-caregiver conflict were associated with a greater risk of behavioral disorders, particularly ADHD + ODD/CD. This group was also five-times more likely to have engaged in sex than their peers and report greater disciplinary problems at school than those without a behavioral disorder. These findings highlight the distinct clinical presentation and adverse outcomes associated with ADHD + ODD/CD among CA-HIV. As more CA-HIV are surviving into adulthood, screening and treatment of mental disorders is needed to ensure they are given the chance to thrive. In addition to youth, interventions should target caregivers due to their impact on youth outcomes.